2020
DOI: 10.36762/jurnaljateng.v18i1.808
|View full text |Cite
|
Sign up to set email alerts
|

Kualitas Fisik Organoleptis, Hardness Dan Kadar Air Pada Berbagai Pakan Ternak Bentuk Pellet

Abstract: This study aims to evaluate the organoleptic quality, hardness and the moisture content of various pelleted animal feeds. This research was uses descriptive method. The pellet feed used was 8 types of pellet feed from various types of livestock, namely; pellet feed for laying hens grower; starter broiler pellet feed; beef pellet feed; dairy cow feed pellets; horse pellet feed; pellet feed of laying ducks; pellet feed for fattening pigs and pellet for fattening sheep are obtained from various animal feed stalls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 5 publications
0
5
0
3
Order By: Relevance
“…Higher water contents increased the risk of mold growth and reducing the qualities of pellet. The maximum water content of pellet is around 12-14% [19].…”
Section: Chemical Properties Of Indigofera Pelletsmentioning
confidence: 99%
“…Higher water contents increased the risk of mold growth and reducing the qualities of pellet. The maximum water content of pellet is around 12-14% [19].…”
Section: Chemical Properties Of Indigofera Pelletsmentioning
confidence: 99%
“…This shows that a good color in animal feed in the form of pellets is pellets that have a bright brown color without spots. For a good pellet odor is an odor that resembles the raw material it is made from, smells fresh and not rancid [20]. The test was conducted at Medan City Industrial Research and Standardization Center based on the SNI 01-2891-1992 test method.…”
Section: Color and Odormentioning
confidence: 99%
“…From Table 5, The hardness of pellet samples made from Indigofera zollingeriana, coconut pulp, rice bran, cassava, molasses, and EM 4 had a hardness value of 5.002. In general, good pellets have a hardness value that ranges from 3.92 to 6.37 [29]. By doing 5 repetitions, it is found that each pellet sample grain has a different hardness value.…”
Section: 002mentioning
confidence: 99%
“…This shows that a good color in animal feed in the form of pellets is pellets that have a bright brown color without spots. For a good pellet odor is an odor that resembles the raw material it is made from, smells fresh and not rancid [20].…”
Section: Color and Odormentioning
confidence: 99%